Respostas

A melhor resposta!
2014-06-03T22:40:25-03:00
A)   (descriminante) = (7²) - 4(2)(5) 
      (descriminante) = 49 - 40 = 9
      x = - (7) + - (a raiz do descriminante)
                       2(2)
       x = -7 + - 3
           4 
       x¹ = -7 - 3 =  -10 : 2 =      
           4         4 : 2 =      2

       x² = - 7 +3 =    - 4  = - 2
                   4          4
3 4 3
b) regra da soma e produto
x¹ = 3 x² = 3
pois 3 x 3 = 9 (c) e 3 + 3 = 6 (b)
c) regra soma e produto x¹ = 7 e x² = -2